Potential Functions and Thermodynamic Properties of UC, UN, and UH - Shuang-Ling Tang; Yu Wang; Qi-Ying Xia; Xue-Hai Ju (Journal of Chemistry)
Potential energy surface scanning for UC, UN, and UH was performed by configuration interaction (CI), coupled cluster singles and doubles (CCSD) excitation, quadratic configuration interaction (QCISD (T)), and density functional theory PBE1 (DFT-PBE1) methods in coupling with the ECP80MWB_AVQZ + 2f basis set for uranium and 6 − 311 + G∗ for carbon, hydrogen, and nitrogen. The dissociation energies of UC, UN, and UH are 5.7960, 4.5077, and 2.6999 eV at the QCISD (T) levels, respectively. The calculated energy was fitted to the potential functions of Morse, Lennard-Jones, and Rydberg by using the least square method. The anharmonicity constant of UC is 0.0047160. The anharmonic frequency of UC is 780.27 cm−1 which was obtained based on the PBE1 results. For UN, the anharmonicity constant is 0.0049827. The anharmonic frequency is 812.65 cm−1 which was obtained through the PBE1 results. For UH, the anharmonicity constant is 0.017300. The anharmonic frequency obtained via the QCISD (T) results is 1449.8 cm−1. The heat capacity and entropy in different temperatures were calculated using anharmonic frequencies. These properties are in good accordance with the direct DFT-UPBE1 results (for UC and UN) and QCISD (T) results (for UH). The relationship of entropy with temperature was established.